Influence of Transition Metal-Doped Clinoptilolite on Tumor Cell Viability: A Correlation with Intercellular Contact Density - Iryna Ivasechko; Olga Klyuchivska; Volodymyr Vasylechko; Olga Vyviurska; Yaroslav Kalychak; Rostyslav Stoika (IEEE NAP-2023, Bratislava, Slovakia, 2023)
Zeolites are biocompatible materials which demonstrated an extended application in different areas of human activity, including medicine and diagnostics. Here we prepared natural zeolite clinoptilolite doped with cations of transition metals, as well as and its If-forms, and investigated the effect of these agents on the viability (metabolic activity measured with MTT assay) and morphological characteristics (fluorescent microscopy) of human tumor cells. The intestinal carcinoma cells of HCT-116 line, growing in the monolayer culture with tight contacts between cells and relatively low proliferation rate, and the acute T-leukemia cells of Jurkat line, growing in a suspension without direct contacts between cells and possessing high proliferation rate, were treated for 24, 48 and 72 h in vitro with H -clinoptilolite, H -clinoptilolite-Tb(III), H-clinoptilolite-Eu(III), and clinoptilolite-Ag(I). Natural clinoptilolite and Doxorubicin-treated cells were used as negative and positive controls of cytotoxic action, correspondingly. Besides, the H-clinoptilolite microcrystals were covered with a mixture of organic components, namely 1,10-phenanthroline and atophan capable of creating complex with rear earth elements (REE) capable of photoluminescence in the visible region. It was found that H -clinoptilolite-REE(III) compositions complexed with organic components demonstrated more intense green and yellow-red luminescence, compared to compositions without such components. When targeting Jurkat cells, H-clinoptilolite-REE(III)-organic compositions can be observed visually. In culture of HCT-116 cells, more intense luminescence was observed under treatment with H-clinoptilolite-REE(III) complexes without an organic component. The detected peculiarities of luminescence of studied complexes might be defined by the influence of the surface of clinoptilolite microcrystals on the intercellular contacts of the suspension and monolayer cells.
Keywords: zeolites; clinoptilolite; rear earth elements; urkat T-leukemia cells; HCT-116 intestinal carcinoma cells; viability (MTT assay); fluorescent microscopy; photoluminescence